Perancangan Dashboard Sistem Informasi Pemeringkatan UBAQA (UB Annual Quality Award) dengan Metode Human Centered Design - Dinda Aditama; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Various plans and strategies were made by Indonesian educational institutions to increase a quality of education, one of them is a work program from Brawijaya University called